Explanatory Factors for Farm Income Diversity in Kalehe District, South Kivu Province, DR Congo - Ciza, Angélique Neema; Manners, Rhys; Schut, Marc; Ngezirabona, Stany Vwima; Lebailly, Philippe (International Journal of Economics and Financial Issues, 2021)
Despite repeated wars and the persistence of feudal land tenure, the agricultural sector is at the center of economic activity for most rural households in the Democratic Republic of Congo. This study aims to assess the competitivity of the agricultural sector in relation to other sectors of economic activity, such as mining. To achieve this aim, it analyses and compares the agricultural incomes of different farmers. It also compares these incomes with their incomes from other sectors of economic activity. This study paid particular attention to two factors of production which may explain the differences in income between farms, namely access to land and family agricultural work labor. A survey was carried out among the 33 dynamic and efficient farmers selected on the basis of the results of previous research carried out in Kalehe territory, sud-Kivu province. Households selected depend almost entirely on agriculture and their agricultural activity makes up 91% of the overall household income. Statistical analysis suggests two important facts. First, there are no relation between the mode of access to land, family labor and rural households' income level. Second, it is only the area farmed and the number of fields that have an impact on overall household income. Keywords: agricultural sector, land tenure, farm income, farm households, poverty, South Kivu JEL Classifications: Q1, Q12, Q15 DOI: https://doi.org/10.32479/ijefi.10793